CNNG: A Convolutional Neural Networks With Gated Recurrent Units for Autism Spectrum Disorder Classification - Jiang, Wenjing; Liu, Shuaiqi; Zhang, Hong; Sun, Xiuming; Wang, Shui-Hua; Zhao, Jie; Yan, Jingwen (Frontiers in Aging Neuroscience, 2022)
As a neurodevelopmental disorder, Autism spectrum disorder (ASD) severely affects the living conditions of patients and their families. Early diagnosis of ASD can enable the disease to be effectively intervened in the early stage of development. In this paper, we present an ASD classification network defined as CNNG by combining of convolutional neural network (CNN) and gate recurrent unit (GRU). First, CNNG extracts the 3D spatial features of fMRI data by using the convolutional layer of the 3D CNN. Second, CNNG extracts the temporal features by using the GRU and finally classifies them by using the Sigmoid function. The performance of CNNG validated on the international public data—Autism Brain Imaging Data Exchange (ABIDE) dataset. According to the experiments, CNNG can be highly effective in extracting the spatio-temporal features of fMRI and achieve a classification accuracy of 72.46%.